Slovenska revija Tovariš in njeni revialni "tovariši" v drugi polovici dvajsetega stoletja - Merljak, Sonja (Javnost (Ljubljana), 2008)
After the Second World War in Slovenia the information age began. For the first time, the Slovenian press which has always developed within the European journalism frame, but always also lagged behind it, caught up with the European media. Many social and political changes influenced the development of the press in Slovenia during that period: firstly and most importantly, the appearance of socialism and self-management, and much later the fall of the Iron Curtain, the end of socialism and the transition to capitalism. Socialism spurred the occurrence of literary journalistic style in the magazine Tovariš. Since journalists could not have openly criticised the political system, they wrapped the criticism in stories about people who suffered injustice.
Keywords: Slovenia; Slovenija; 1945/1991; časopisi; journalism; novinarstvo; politične razmere; kritika; nadzor; cenzura